Application of Replica Ornstein-Zernike equations in studies of the adsorption of electrolyte mixtures in disordered matrices of charged particles - Lukšič, M.; Trefalt, G.; Hribar-Lee, B. (Condensed Matter Physics, 2009)
The Replica Ornstein-Zernike (ROZ) equations were used to study the adsorption of ions from electrolyte mixtures. The adsorbent was represented as a quenched primitive model +1:-1 size symmetric electrolyte, while the mobile particles were ions differing in charge and/or size. The ROZ equations in hypernetted-chain (HNC) approximation were tested against new Monte Carlo results in the grand canonical ensemble; good agreement between the two methods was obtained. The ROZ/HNC theory was then used to study the exclusion coefficients as a function of size and/or charge asymmetry of the annealed ions. Реплiчне рiвняння Орнштейна-Цернiке (РОЦ) застосоване для вивчення адсорбцiї iонiв iз сумiшей електролiтiв. Адсорбент розглядається у виглядi замороженої примiтивної +1:-1 моделi розмiрно симетричного електролiту, тодi як рухомi частинки – це iони, що вiдрiзняються зарядом та/або роз- мiрами. Данi, що отриманi з рiвняння РОЦ у гiперланцюжковому наближеннi (ГЛН), порiвняно з но- вими результатами Монте-Карло моделювання у великому канонiчному ансамблi i виявлено хороше узгодження мiж обома методами. Теорiю РОЦ/ГЛН далi було використано для вивчення коефiцiєнтiв виключення, в залежностi вiд параметрiв розмiрної та/або зарядової асиметрiй нерухомих iонiв.